Metformin Suppresses the Progress of Diabetes-Accelerated Atherosclerosis by Inhibition of Vascular Smooth Muscle Cell Migration Through AMPK–Pdlim5 Pathway - Yan, Yi; Li, Ting; Li, Zhonghao; He, Mingyuan; Wang, Dejiang; Xu, Yingyi; Yang, Xuewen; Bai, Yuanyuan; Lao, Yi; Zhang, Zhiyong; Wu, Wei (Frontiers in Cardiovascular Medicine, 2021)
Backgrounds: Our previous work revealed that AMP-activated protein kinase (AMPK) activation inhibits vascular smooth muscle cell migration in vitro by phosphorylating PDZ and LIM domain 5 (Pdlim5). As metformin is an AMPK activator, we used a mouse vascular smooth muscle cell (VSMC) line and a Myh11-cre-EGFP mice to investigate whether metformin could inhibit the migration of VSMCs in vitro and in a wire-injury model in vivo. It is recognized that VSMCs contribute to the major composition of atherosclerotic plaques. In order to investigate whether the AMPK–Pdlim5 pathway is involved in the protective function of metformin against atherosclerosis, we utilized ApoE−/− male mice to investigate whether metformin could suppress diabetes-accelerated atherosclerosis by inhibition of VSMC migration via the AMPK–Pdlim5 pathway. Methods: The mouse VSMC cell line was exogenously transfected wild type, phosphomimetic, or unphosphorylatable Pdlim5 mutant before metformin exposure. Myh11-cre-EGFP mice were treated with saline solution or metformin after these were subjected to wire injury in the carotid artery to study whether metformin could inhibit the migration of medial VSMCs into the neo-intima. In order to investigate whether the AMPK–Pdlim5 pathway is involved in the protective function of metformin against atherosclerosis, ApoE−/− male mice were divided randomly into control, streptozocin (STZ), and high-fat diet (HFD)-induced diabetes mellitus; STZ+HFD together with metformin or Pdlim5 mutant carried the adenovirus treatment groups. Results: It was found that metformin could induce the phosphorylation of Pdlim5 and inhibit cell migration as a result. The exogenous expression of phosphomimetic S177D-Pdlim5 inhibits lamellipodia formation and migration in VSMCs. It was also demonstrated that VSMCs contribute to the major composition of injury-induced neointimal lesions, while metformin could alleviate the occlusion of the carotid artery. The data of ApoE−/− mice showed that increased plasma lipids and aggravated vascular smooth muscle cell infiltration into the atherosclerotic lesion in diabetic mice were observed Metformin alleviated diabetes-induced metabolic disorders and atherosclerosis and also reduced VSMC infiltration in atherosclerotic plaques, while the Pdlim5 phospho-abolished mutant that carried adenovirus S177A-Pdlim5 undermines the protective function of metformin. Conclusions: The activation of the AMPK–Pdlim5 pathway by metformin could interrupt the migratory machine of VSMCs and inhibit cell migration in vitro and in vivo. The maintenance of AMPK activity by metformin is beneficial for suppressing diabetes-accelerated atherosclerosis.